Altered Cast Impression Technique for a Molar Supported with Two Dental Implants: A Technical Report - Elaheh Beyabanaki (Mashhad University of Medical Sciences, 2021)
Introduction: Since first molars are among the first lost teeth, is it common to restore them with dental implants. Considering the amount of remaining mesiodistal space, a wide/medium-diameter implant or two medium/narrow-diameter implants are used in this region. However, the impression procedure can be complicated when two closely adjacent implants are placed.Technical Report: A patient with two narrow-diameter implants placed in the mandibular right first molar referring for prosthetic restoration. It was not possible to secure both impression copings simultaneously for conventional impression making due to the proximity of implants and the width of impression copings. Therefore, it was decided to follow the altered cast procedure after making two implant impressions, preparing casts, and selecting abutments separately. The preparation of the index for the final cast is possible via using two methods of splinting the final abutments or resin copings intraorally. Conclusion: In case that the position of the implants is not ideal, the selection of the proper impression technique is important for achieving a successful prosthetic outcome. The use of the altered cast impression technique in the presence of two adjacent implants in the molar area is helpful for a successful treatment.